Sophrosyne and the rhetoric of self-restraint : polysemy and persuasive use of an ancient Greek value term - Rademaker, Adriaan, 1965- (Mnemosyne, Supplements, 2005)
While of paramount importance to Ancient Greek society, sophrosyne , the value of self-restraint, constitutes a notoriously complex concept, and provides the speaker of Ancient Greek with a subtle instrument for verbal persuasion. This study provides a new description of the semantics of sophrosyne in Archaic and Classical Greek, based on a model from the field of cognitive linguistics. Besides, the volume shows how such a semantic description can contribute to the analysis and study of our sources: it investigates how speakers in our texts (ab)use the term to achieve their ends, covering most of the main texts, and culminating in a chapter on the dialogues of Plato.